Bibliometric analysis on islamic spiritual care with special reference to prophetic medicine or al-Ṭibb al-Nabawī - Mohd Marzuki, Zunaidah; Ahmad Fuad, Nurulhaniy; Abdul Khaiyom, Jamilah Hanum; Mohd Adnan, Normala; Mokhtar, Aida (International Islamic University Malaysia, 2024)
This study focuses on a bibliometric analysis that explores trends on Prophetic medicine (al-ṭibb al-nabawī) within Islamic spiritual care. Due to the scarcity of literature, it utilised “Islamic Spiritual Care” as a search term on Dimensions.ai, rather than “Prophetic Medicine” or “Ḥadīth.” Initially, 325 titles were identified, with 56 of them meeting the criteria for analysis. The data was then analysed using the Biblioshiny interface of the Bibliometrix R package. The results reveal a steady rise in Islamic spiritual care studies over the past decade, despite notable fluctuations. The exploration of Prophetic medicine within the framework of spiritual care lacks sufficient emphasis, as indicated by the analysis of the 56 pertinent sources, particularly from the most frequent words and co-occurrence network map of authors’ keywords. This research, to the knowledge of the authors, is a pioneering bibliometric analysis in the field.